Pemetaan Kerusakan Jalan Berbasis Fotogrametri Menggunakan UAV - Alhamdi, Mulki; Dwi Arini; Dwi Marsiska Driptufany; Defwaldi Defwaldi; Fajrin Fajrin (Jurnal Sains dan Ilmu Terapan, 2025)
Transportation infrastructure is essential for economic development and social activities. In areas like the Koto Tangah Batu Hampa–Barulak road in Akabiluru District, severe road damage hampers accessibility. Traditional manual inspections for assessing pavement damage are time-consuming and inefficient. This study utilizes Unmanned Aerial Vehicles (UAVs) to observe the distribution and classification of road surface damage through aerial imagery.A descriptive quantitative method was applied by comparing direct field measurements with UAV-captured photos. The process included aerial image acquisition, field validation, and spatial analysis using on-screen digitization. The study identified 55 damage points along a 350-meter road segment, with a total road surface of 2,087.61 m² and damaged area of 578.94 m². Four types of damage were detected: Edge Cracks, Potholes, Alligator Cracks, and Patches. The results confirm that UAV-based photogrammetry offers a fast, accurate, and efficient approach to monitoring road conditions. This method provides valuable data for infrastructure planning and maintenance, especially in remote or large-scale areas.